Case Comment – Cumberland v Accident Compensation Corporation - Williams, Anthea (Victoria University of Wellington Law Review, 2014)
In Cumberland v Accident Compensation Corporation, the Court of Appeal held that where a mother is denied the information that her foetus is disabled, and thus loses the opportunity to terminate the pregnancy, the "continuing pregnancy" can be a personal injury covered by the Accident Compensation scheme. This article examines the judgment and argues the Court of Appeal has extended New Zealand case law on "wrongful births" without explicitly acknowledging this. The author suggests that, by focussing purely on the physical effects on the mother and her lost opportunity to determine the medical treatment given to her, the Court has avoided the value laden approach that has plagued other wrongful birth cases.